The Role of ESG and Governance Quality in Shaping Fintech Development Across MENA: Evidence from Empirical Data - Abdo, Khawla Kassed (International Journal of Energy Economics and Policy, 2026)
This article investigates the effect of ESG performance and governance quality on FinTech adoption in energy companies from the Middle East and North Africa region (MENA). The study, based on 1,616 firm-year observations over the period of 2010 to 2023 seeks to understand the antecedents of FinTech adoption in sub-sectors including Oil & Gas (O&G), Solar, Wind, Hydro, Nuclear, Bioenergy and Utilities by examining extent board characteristic and regulatory compliance signaling effect of transparency theories and ESG initiatives. The study found that the superior ESG higher ESG performance enhances significantly the adoption of Fintech according to Fixed-Effects, Random Effects, and Dynamic Panel data inference. Firms with smaller, more independent and more gender-diverse boards and strong compliance and transparency mechanisms are better able to embrace digital innovations. There are particularly strong ESG–FinTech connections among renewable and utility companies, highlighting the important link between sustainability practices and digital transformation. Implications are drawn in line with the Resource-Based View, stressing ESG and governance as internal capabilities, and Stakeholder Theory emphasising transparency and accountability towards external stakeholders. For energy leaders and policymakers, ESG-motivated governance reforms can help to speed up the take-up of FinTech, encourage innovation, as well as ensure MENA’s energy sector has sustainable futureproofing.